2013
DOI: 10.1016/j.enconman.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical programming model for heat exchanger design through optimization of partial objectives

Abstract: Mathematical programming can be used for the optimal design of shell-and-tube heat exchangers (STHEs). This paper proposes a mixed integer non-linear programming (MINLP) model for the design of STHEs, following rigorously the standards of the Tubular Exchanger Manufacturers Association (TEMA). Bell-Delaware Method is used for the shell-side calculations. This approach produces a large and non-convex model that cannot be solved to global optimality with the current state of the art solvers. Notwithstanding, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…But this type of heat exchanger has some inherent drawbacks, such as a large pressure drop in the shell side and a dead zone in the back of the segmental baffles, and leading to a serious fouling and high risk of vibration failure on tube bundles [2][3][4][5][6]. A number of new methods were proposed to overcome the above-mentioned drawbacks in shell-and-tube heat exchangers with segmental baffle [7][8][9][10][11][12][13]. STHX with helical baffles (STHXsHB) was firstly proposed by Lutcha and Nemcansky [14].…”
Section: Introductionmentioning
confidence: 99%
“…But this type of heat exchanger has some inherent drawbacks, such as a large pressure drop in the shell side and a dead zone in the back of the segmental baffles, and leading to a serious fouling and high risk of vibration failure on tube bundles [2][3][4][5][6]. A number of new methods were proposed to overcome the above-mentioned drawbacks in shell-and-tube heat exchangers with segmental baffle [7][8][9][10][11][12][13]. STHX with helical baffles (STHXsHB) was firstly proposed by Lutcha and Nemcansky [14].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of heat recovery is critical to solve the problem of the efficient use of energy and, consequently, to promote the reduction of gaseous emissions and consumption of oil and natural gas, since the reduction of energy consumption is closely linked to improvement of heat transfer (Cheng and Liang, 2012a;Kaluri and Basak, 2011;Onishi et al, 2013a;Wang et al, 2011). Thereby, harnessing energy from process streams through thermal integration between heat exchangers and cooling and/or heating systems is one of the most effective ways to reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…Example 1, originally proposed by Shenoy, is based on the minimization of heat transfer area, and Example 2, originally presented by Mizutani et al, involves the minimization of the total annualized cost. Both examples were solved by Ravagnani and Caballero and Onishi et al using an MINLP formulation. The comparison of our results and Ravagnani and Caballero and Onishi et al must consider some differences: The tube‐side correlations in our model are different from the correlations used by Ravagnani and Caballero and Onishi et al Our model for the evaluation of the tube‐side convective heat transfer coefficient encompasses all flow regimes.…”
Section: Comparison With Results From the Literaturementioning
confidence: 99%
“…Among different alternatives using mathematical programming, Jegede and Polley presented a nonlinear programming model where the independent variables are the tube‐side and shell‐side heat transfer coefficients (or a convective heath transfer coefficient and the area). In turn, Mizutani et al, Ravagnani and Caballero, and Onishi et al considered some optimization variables to be discrete, which yielded nonconvex mixed‐integer nonlinear programing (MINLP) problems. In addition, Gonçalves et al showed that the nonlinear equations of the heat exchanger model based on the Kern method can be reformulated as a mixed‐integer linear programming problem (MILP), whose solution is therefore global.…”
Section: Introductionmentioning
confidence: 99%